2016
DOI: 10.1002/ece3.1931
|View full text |Cite
|
Sign up to set email alerts
|

Using Africa's protected area network to estimate the global population of a threatened and declining species: a case study of the Critically Endangered White‐headed Vulture Trigonoceps occipitalis

Abstract: The White‐headed Vulture Trigonoceps occipitalis (WhV) is uncommon and largely restricted to protected areas across its range in sub‐Saharan Africa. We used the World Database on Protected Areas to identify protected areas (PAs) likely to contain White‐headed Vultures. Vulture occurrence on road transects in Southern, East, and West Africa was adjusted to nests per km2 using data from areas with known numbers of nests and corresponding road transect data. Nest density was used to calculate the number of WhV ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 41 publications
3
25
0
Order By: Relevance
“…We further assumed that small CAs, with sufficient savanna to support only a single pair of a given species, would be occupied only intermittently. Following Murn et al (2016), we took a conservative approach to estimating the number of breeding pairs present, by excluding CAs where the amount of savanna was less than double that required to support one pair of the target species.…”
Section: Abundance Estimatesmentioning
confidence: 99%
See 2 more Smart Citations
“…We further assumed that small CAs, with sufficient savanna to support only a single pair of a given species, would be occupied only intermittently. Following Murn et al (2016), we took a conservative approach to estimating the number of breeding pairs present, by excluding CAs where the amount of savanna was less than double that required to support one pair of the target species.…”
Section: Abundance Estimatesmentioning
confidence: 99%
“…To fully appreciate the implications of farmland conversion for such species it is important to determine the degree to which they are dependent on protected areas, their density within savanna, and hence the number of pairs each PA is capable of supporting. In a detailed case study, Murn et al (2016) applied this approach to the White-headed Vulture Trigonoceps occipitalis, a species now largely confined to PAs throughout its global range. Their findings highlight the fragmentary nature of the species' global distribution, showing that 78% of occupied PAs are each likely to support fewer than five breeding pairs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that vulture populations have declined, particularly in Africa (Virani et al 2011, Ogada et al 2012, Murn et al 2016, Ogada et al 2016. Accordingly, most species are now listed on the International Union for the Conservation of Nature and Natural Resources (IUCN) Red List as Endangered or Critically Endangered (IUCN 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The species is critically endangered [18] and with a global population of approximately 5500 birds [19], they are difficult to find. To estimate the detection probability of large savannah raptors and the factors that affect it, in this study we used encounter rates of white-headed vultures during surveys in areas of known vulture occupancy.…”
Section: Introductionmentioning
confidence: 99%